Phenomenology in Japan
IV, 112 p.
Keywords: Since the introduction of phenomenology to Japan in the 1910's, Japan has steadily become a major international site for both original and scholarly phenomenological work. Phenomenology in Japan presents several of Japan's leading phenomenologists, studied in both the Buddhist and Western thought, who bring to bear their unique backgrounds on our rich fields of experience. These contributions converge in novel ways on the problem of `dualist', and draw on resources within the phenomenological tradition to respond to its challenges.